Prevalence and determinants of hypertension control among almost 100 000 treated adults in the UK - Tapela, N; Collister, J; Clifton, L; Turnbull, I; Rahimi, K; Hunter, DJ (BMJ, 2021)
Objective To identify factors associated with hypertension control among treated middle-aged UK adults.